Feasibility and acceptability of Otago Exercise Programme and Prevention of Falls for Adults with Intellectual Disability: a multiple case study design. (2nd June 2019) - Hale, Leigh; Vollenhoven, Emile; Caiman, Lisa; Dryselius, Alice; Buttery, Yvette
Abstract : Background/Aims: Many people with intellectual disability fall frequently. Understanding fall prevention intervention characteristics will assist efficacy trials to target appropriate people. An exploration of two exercise-based fall prevention interventions is reported, focusing on viability and acceptability. Methods: A multiple case study of adults with intellectual disability completing either the group Otago Exercise Programme or the Prevention of Falls for Adults with Intellectual Disability intervention was performed. Integrated data sources were used: semi-structured interviews with participants and support workers, observations, attendance/adherence, falls, adverse events and balance measures. Results: In total, seven adults with varying intellectual disability levels participated. Overall, three themes enabled understanding of suitability of people to each intervention: suitability of the exercises; role of the environment; and benefits to participants. Conclusions: Educating adults with intellectual disability and their support workers of the importance of regular exercise is key to participation. Both programmes required high levels of support and prioritisation to ensure exercises occurred and were carried out safely.